Integration of Local Wisdom Values of the Nadran Tradition in Indonesian Language Learning: A Systematic Literature Review - Sylpia Ayuningrum; Khaerudin Kurniawan; Dadang S. Anshori (Universitas Muhammadiyah Malang, 2026)
Indonesian language learning in junior high schools still faces a fundamental problem in the form of a disconnect between the teaching material and the socio-cultural realities of students. Students often view language only as a formal communication tool, not a means of character building and cultural meaning. This study aims to identify the educational values ​​of the Nadran tradition and explore the possibility of integrating them into local wisdom-based Indonesian language learning. The method used is a Systematic Literature Review (SLR) of 15 scientific articles obtained through Google Scholar, Garuda, and DOAJ databases, supplemented by interview data, observations, and field documentation in the coastal areas of Cirebon and Indramayu. Analysis was carried out through thematic classification to identify the Nadran tradition's central values relevant to the educational context. The results show that Nadran contains four central educational values, namely religiosity, cooperation, cultural symbolism, and ecological awareness, which are highly relevant to be developed in text-based Indonesian language learning. Integrating these values ​​has been proven to increase learning motivation, literacy understanding, and strengthen students' character. This study concludes that the Nadran tradition is a cultural heritage and a strategic pedagogical potential to realize Indonesian language learning that is contextual, humanistic, and rooted in the nation's cultural values.